Gut microbiota compositional profile and serum metabolic phenotype in patients with primary open-angle glaucoma. (February 2020) - Gong, Haijun; Zhang, Simin; Li, Qiguan; Zuo, Chengguo; Gao, Xinbo; Zheng, Bingru; Lin, Mingkai
Abstract: The gut microbiota (GM) and its influence on host metabolism are considered to be an environmental factor that contributes to the progression of many immune and neurodegenerative diseases. However, the features of the GM and serum metabolites in Primary open-angle glaucoma (POAG) patients have not been clearly elucidated. The purpose of this research is to explore the gut microbial composition and serum metabolic phenotype in POAG patients. 16S rRNA V4 genes of bacteria from the fecal samples of 30 POAG patients and 30 healthy subjects were sequenced by the Illumina MiSeq platform and then analyzed by QIIME. Their serum samples were analyzed by gas chromatography/mass spectrometry (GC-MS)-based metabolomics. The association between gut microbial species and host circulating metabolites and clinical phenotypes was also analyzed. Compared with controls, f Prevotellaceae, g unidentified Enterobacteriaceae, and s Escherichia coli increased the most in POAG patients, whereas g Megamonas and s Bacteroides plebeius significantly decreased in POAG patients . The alteration of the endogenous metabolomic profile in POAG patients included five amino acids or dipeptides, two hormone derivates, one purine derivative, one bile acid derivative and one organic acid. It also showed that citric acid was positively correlated with Megamonas, whereas L-γ-Glutamyl-L-alanine, MHPG, cholic acid glucuronide and hypoxanthine were negatively correlated with Megamonas . Mean visual acuity was negatively correlated with Blautia, mean VF-MD was negatively correlated with Faecalibacterium, and average RNFL thickness was positively correlated with Streptococcus . Our results revealed that there was a distinct difference in GM composition and serum metabolic phenotype between POAG patients and healthy individuals. This finding suggests the potential correlations between the GM and serum metabolites in the pathogenesis of glaucoma and thus provides new insight into the GM-targeted interventions of this disease. Highlights: POAG patients have different gut microbiota and serum metabolites with healthy subjects. Gut microbiota and host metabolism might be linked with glaucoma. Gut microbiota and metabolites-targeted interventions of glaucoma should be considered in future.